Влияние защищенного подхода на выбор расчетного тока однофазного короткого замыкания в электрических высоковольтных сетях - Нижевский, Илья Викторович; Нижевский, Виктор Ильич; Березка, Сергей Константинович; Бехруз, И.; Насриддини, Саид (НТУ "ХПИ", 2016)
Исследовано влияние длины пролета и числа опор защищенного подхода примыкающих к подстанции линий электропередачи на выбор расчетного тока однофазного короткого замыкания в электрической высоковольтной сети. Показано, что рост длины пролета и (или) сопротивления заземлителя опоры увеличивает сопротивление заземления системы “трос-опоры”. Использование результатов исследований позволяет более точно определять значение расчетного тока однофазного короткого замыкания.

On the base of calculations and studies the resistance grounding device substation changes consisting of the substation earthing system and earthing "wiretower", depending on the parameters of the last ones is analyzed. The effect of the span length, the number of towers on a protective length each transmission lines to substations and on the selection of the rated current of single-phase short circuit in an electrical high-voltage networks. An increase in the span length and (or) resistance grounding device increases the resistance of "wire-tower". Studies carried out for the actual range of variation of the circuit parameters, showed that the resistance of the earth electrode substation substantially affects the distribution of single-phase shortcircuit current in the circuit. Using the results of research can more accurately determine the value of the rated current of single-phase short circuit. The results are recommended to take into account in the design of grounding systems at substations
The effect of protective length on a choice of current of single-phase short circuit in electric high-voltage networks
Keywords: подстанция; заземлитель; система “трос-опоры”; длина пролета; число опор; substation; grounding device; system "wire-tower"; span length; number of towers